Tinjauan Literatur: Dampak Kesehatan Akibat Paparan Fly Ash dari Pembakaran Batu Bara pada Pekerja Industri - Rina Widya Astuti; Izzatul Alifah Sifai2 (Journal Occupational Health Hygiene and Safety, 2025)
Over the past three decades, global coal consumption has increased significantly. Indonesia has become one of the largest consumers in the ASEAN region. One of the primary by-products of coal combustion is fly ash, a fine particulate material that contains various heavy metals such as lead, arsenic, chromium, and cadmium. Although the concentrations are relatively low, long-term exposure to fly ash poses serious health risks. This study aims to examine the health impacts of fly ash exposure on industrial workers, particularly those working in coal-fired industry. The method used is a narrative literature review by analyzing articles from databases such as Google Scholar, PubMed, and ScienceDirect, published between 2015 and 2025. The results show that fly ash exposure can lead to various health issues, including contact dermatitis, elevated blood lead levels, DNA damage, hemolysis, and apoptosis of bronchial cells. The severity of these impacts is influenced by particle size, chemical composition, duration of exposure, and the use of personal protective equipment (PPE). Therefore, further research and stricter occupational safety policies are needed to protect the health of industrial workers.